The European regulation on AI in the face of the biases and risks of algorithmic discrimination in migration contexts - Encarnación La Spina (Revista CIDOB d'Afers Internacionals)
The increasing institutionalisation of artificial intelligence (AI) is a social problem of particular concern for the most vulnerable groups, such as migrants and asylum seekers. While global migration contexts face tight security control and an extensive digital transition, the European regulation on AI is still too limited in scope to counteract the negative impacts of the design and training of algorithms. With that in mind, this paper provides a critical review of how AI-driven systems are introduced into European migration control and management, and analyses why the new legal framework for AI does not do enough to prevent the discriminatory impact of biases, stereotypes and risks associated with the asymmetric power dynamics and the structures of social injustice underlying migration.